Analisis dasar pertanian: peranan sektor pertanian dalam Pelan Induk Perindustrian - Abdul Rashid, Zakariah (Penerbit Universiti Kebangsaan Malaysia, 1992)
The rapid expansion in the manufacturing sector has resulted in the declining relative significance of the agricultural sector, which has always been misunderstood as the neglected sector despite its increasing absolute contribution. The paper discusses the misconception by explaining the complementary roles of agriculture sector in the Malaysian industrialisation. Particularly, in an industrialisation where the emphasis is still on the down-stream processing of agriculture, agriculture sector supplies a good deal of input to agro-based industries. Results of input-output and linkage analyses strengthen the above preposition. Similarly, input-output sensitivity analysis of various types of final demand shows that final demand on agro-based products generates bigger impact on sectoral output compared to that of non-agrobased products. In summary, agriculture sector has a unique role to play in the industrialisation of Malaysia.